Hubungan Berat Badan Lahir dengan Ruptur Perineum Persalinan Normal di Praktek Bidan Mandiri Lusi Marbun Kab. Simalungun Tahun 2022 - Debora Debora; Nur Azizah; Rosmani Sinaga; Marlina Simbolon; Junida Laia (NAJ Nursing Applied Journal, 2025)
Rupture of the perineum is one of the common complications in vaginal delivery that can increase the risk of postpartum hemorrhage, infection, and maternal death. One of the factors that contribute to the occurrence of perineal rupture is the baby's birth weight. Babies with a birth weight of ≥4000 grams can cause greater pressure on the mother's birth canal, increasing the likelihood of tearing of perineal tissue. In Indonesia, 75% of mothers who give birth vaginally experience perineal lacerations, and postpartum bleeding is still the leading cause of 40% of maternal deaths. This study aims to determine the relationship between infant birth weight and the incidence of perineal rupture in normal childbirth at the Lusi Marbun Independent Midwife Practice, Simalungun Regency in 2022.This study uses an observational analytical design with a case control approach. A sample of 30 maternity mothers was selected using the total sampling method. The data were analyzed using the Chi-square test to determine the relationship between birth weight and perineal rupture. The results showed that the majority of babies had a birth weight of <4000 grams (63.3%) and the majority of mothers experienced a second degree perineal rupture (70%). The results of bivariate analysis showed that there was a significant relationship between birth weight and the incidence of perineal rupture (p-value = 0.000). There is a significant relationship between birth weight and the incidence of perineal rupture. The greater the baby's weight, the higher the risk of perineal rupture in the mother during childbirth. It is important for health workers to carry out early detection of fetal weight, provide nutrition education during pregnancy, and prepare for the delivery process optimally to minimize the risk of complications.